Peningkatan Pemahaman Pada Perlindungan Hukum Transaksi Online bagi Siswa – Siswi SMA Kesatrian Semarang - Supriyadi, Supriyadi; Muryati, Dewi Tuti; El Ula, Khaidar Alifika (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service, Universitas Semarang chose SMA Ksatrian Semarang. The Ksatrian High School Semarang was chosen as the location for community service activities with the topic Understanding Consumer Protection in Online Buying and Selling Transactions, considering that online shopping consumers are generally young people, teenagers, including students in high school who already have very adequate internet facilities. The Semarang City area is one of the areas with very adequate internet facilities in Central Java Province. Teenagers who are still unable to understand the bad side of online transactions will become angry for consumers so that understanding is still very much needed, maybe even very important. Consumers who transact through online channels in addition to getting convenience and practicality, often also experience losses on online selling transactions. While the method used by the service team is the Socialization method, which explains the rules and sanctions applied in the use of electronic media, especially in business activities, the Discussion method so that participants better understand the material presented. Through discussion, socialization is not just a transfer of knowledge but can share experiences and problems that are being faced by partners. Questionnaire method This method is used to find out how much interest Semarang Kesatrian High School students are about understanding protection in online transactions. Solutions to problems related to buying and selling transactions through the online system to students as consumers are carried out by providing socialization and exposure to legal materials, ranging from understanding consumer legal protection, consumer losses, legal basis for online buying and selling transactions, legal remedies consumer protection and consumer dispute resolution